PENGARUH HIJAB PEREMPUAN PADA TATA RUANG RUMAH TINGGAL MUSLIM - Rahmah, Sukmayati (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2012)
Women are the beings who guarded her nakedness than most men. Sowomen have a more privacy rooms than others. By keeping the hijab asmuch as possible, the activities of the household can work well withoutfear of nakedness is maintained. It is very clear that in islamic law, theorders keep the hijab has been described in the Holy of Quran and Sunnah.So the role of architectural space is very important in presenting a spacethat could keep the nakedness of women in the home. As we know thatspace as a place of human activities, one of which is accommodating theactivity of female residents in homes with a due regard to any restriction orhijab women in islam. This paper uses the theory as a method of approachand observe the formation of the muslim family residential. So the studycan show the attention to architectural form hijab women in spatialarrangement. Spatial planning with respect to public and private space,Â the circulation of the house and used a room divider has major role inÂ maintaining and cover the nakedness of the inhabitants, especially womenin home. Separation of public and private space as one of the applicationsthat are close the genitals. So the concept of study of this theory can bereference in designing the lay out in residences are islamic.